Safe limits on work hours for the nursing profession: a rapid evidence review - Scott-Marshall, Heather Katherine (Frontiers in Global Women's Health, 2024)
Persistent staffing shortages in health care driven by years of inadequate funding and deficiencies in human resources planning, which overlooked the impacts of population aging, have converged into a crisis in health care settings. An essential consequence of the widespread and growing staffing shortfalls in health care has been increased pressure on nurses to work longer hours. The present rapid review has two major objectives: (1) to systematically review and synthesize evidence considering the health and human consequences of excessive work hours, work-related fatigue and associated occupational health and safety hazards; and, (2) to identify policies and practices that demonstrate efficacy in managing or mitigating the adverse effects of occupational fatigue. Findings show that shifts lasting longer than 12 h elevate the risk of occupational fatigue, leading to several fatigue-based hazards. Despite governmental restrictions on long work hours and occupational fatigue in safety-critical industries such as transport, aviation, and nuclear sectors, health care remains largely unregulated in this regard. Ensuring safe and high-quality care over the long term requires implementing adequate regulatory supports for work hour limits for nurses. These measures not only improve workplace satisfaction but also enhance patient outcomes, ultimately fostering a healthier and more resilient health care system.